Matonabbee (ca. 1736-1782) - Glover, Richard (ARCTIC, 1983)
. one may doubt whether either . [Sitting Bull or Tekumseh] was abler than the Chipewyan diplomat, trader, and explorer, Matonabbee - Samuel Hearne's guide on his final, and successful, journey to the Coppermine River. . Nearly all we know about him comes from Hearne, who was so long employed at that post. . At Churchill Matonabbee learned much. He became a "perfect master" of the Cree language, as well as his native Chipewyan; he "made some progress in English" too. Hearne records the interesting fact that he could "tell a better story of our Saviour's birth and life than one half of those who call themselves Christians" - but he never believed it! However, adds Hearne, no man could "have been more punctual in the performance of a promise" and his "adherence to truth" was "scrupulous." Physically, he grew to be "nearly six feet high", and he was "one of the finest and best proportioned men" that Hearne ever saw. He certainly did not lack courage. In view of these qualities Ferdinand Jacobs made a good choice in selecting Matonabbee "when but a youth as an Ambassador" to make peace between the Chipewyans and the far western Crees of Athabasca. This task was dangerous, because the Crees were treacherous, and slow, because the tribal feud was old and deep-seated. But Matonabbee was alert enough to baffle all Cree plots, and brave and patient enough to repeat his visits to them "for several years successively; and at length, by a uniform display of his pacific disposition and by rendering a long train of good offices to those Indians, in return for their treachery and perfidy," he succeeded "in not only bringing about a lasting peace, but also of establishing a trade and reciprocal interest between the two nations." It was doubtless during these early peace-making journeys that Matonabbee took up the career of being one of those "Leading Indians" who were so important in the fur trade. .